2003
DOI: 10.1177/03635465030310011801
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Flexibility as a Risk Factor for Developing Muscle Injuries in Male Professional Soccer Players

Abstract: Preseason hamstring and quadriceps muscle flexibility testing can identify male soccer players at risk of developing hamstring and quadriceps muscle injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
442
6
47

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 601 publications
(505 citation statements)
references
References 31 publications
10
442
6
47
Order By: Relevance
“…Core stability may also be a factor in ACL injury [29]. Several recent studies have demonstrated gender differences in core stability [6,7,30] and increased risk of injury related to that difference [30][31][32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Core stability may also be a factor in ACL injury [29]. Several recent studies have demonstrated gender differences in core stability [6,7,30] and increased risk of injury related to that difference [30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous papers have established that women cut and land with their knees in valgus, placing their knees at risk for injury [1][2][3][4]. Descriptive data exist for physical characteristics of elite male soccer players [5][6][7]; however, there is no published information regarding the musculoskeletal characteristics of elite female soccer players.…”
Section: Introductionmentioning
confidence: 99%
“…Así, diversos trabajos han observado que el rendimiento deportivo declina tanto con el ROM extremo "hipermovilidad" (Gannon y Bird, 1999;Snyder, McLeod y Hartman, 2006) como con el ROM limitado por una menor extensibilidad muscular "cortedad muscular" (Young, Clothier, Otago, Bruce y Liddell, 2003;Rahnama, Lees y Bambaecichi, 2005;Zakas, Vergou, Zakas, Grammatikopoulou y Grammatikopoulou, 2002;Zakas, Vergou, Grammatikopoulou, Sentelidis y Vamvakoudis, 2003). Además, la cortedad muscular ha sido correlacionada con la lesión muscular (Bradley, Olsen y Portas, 2007;Dadebo, White y George, 2004;Ekstrand, Wiktorsson, Oberg y Gillquist, 1982;Rahnama et al, 2005;Witvrouw, Danneels, Asselman, D'Have y Cambier, 2003), la lesión ligamentosa como el esguince de tobillo (Ekstrand y cols., 1982;Pope, y cols., 1998; Okamura y cols., 2014) y la rotura del ligamento cruzado anterior (Ellera, Vieira y Becker, 2008), y la lesión por sobrecarga como la fascitis plantar, la tendinopatía rotuliana y aquilea, la periostitis tibial, el síndrome de la cintilla iliotibial y el síndrome de dolor femoropatelar (Witvrouw, Mahieu, Roosen y McNair, 2007;Probst, Fletcher y Seeling, 2007;Johanson, Baer, Hovermale y Phouthavong, 2008).…”
Section: Introductionunclassified
“…The effects of fatigue on balance can appear immediately after the performance of exercise and tend to decrease over time 16 . Therefore, balance and the performance of functional tasks decrease following fatiguing exercise 17 .…”
Section: Introductionmentioning
confidence: 99%